PENERAPAN GRABBER PADA OPTICAL FLOW UNTUK MENGGERAKKAN CURSOR MOUSE MENGGUNAKAN BOLPOIN - Anton Setiawan Honggowibowo; Sapto Aji Wibowo (Institut Teknologi Dirgantara Adisutjipto, 2015)
Technological developments in the field of computers getting faster requires the ability of each person to be able to follow the progress of computer development. Computer vision applications is an application that allows the computer to have the ability to be able to capture and understand the data, such as image and make decisions based on the data from the real object movement that was in front of the webcam and then the data obtained is processed in accordance with user needs. Digital image of a real object is captured by a webcam can be done in various ways making objects. In this research, object retrieval by utilizing activity in this object is that caught on webcam pen is through the form and motion of objects. Once an object is detected then the object is to move the cursor on a computer. To be able to perform image processing, this application uses OpenCV components. Meanwhile, to be able to perform tracking of the cursor object using optical flow method. Cursor moves when the pen has a rectangular sides and parallel to the pen position frame of grabber.